Pesona Jawa dalam Puisi Rusia - Widyastuti, Thera; Limbong, Banggas (Paradigma: Jurnal Kajian Budaya, 2016)
This research will analyze Russian poems by using the approach of sociology of literature. Poetry is a popular form in Russian literature. The presence of the poets with their works make people in the world know Russian literature. The poets’s journey to all over the world provide experiences that inspire their works. Nusantara as a region famous for its natural resources has attracted Europeans, and has inspired the Russian poets Esperovich Esper Ukhtomsky, Konstantin Dmitriyevich Balmont, Valery Yakovlevich Bryusov and Vladimir Yurievich Elsner. They wrote poems the beauty of the natural and cultural heritage, especially in Java. Borobudur, traditional music, traditional dance, and Botanical Gardens became theme in their poetry.